2023
DOI: 10.1021/acsami.3c11748
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the Microstructure and Current Density of the Li/Garnet Interface

Cheng Ouyang,
Hongpeng Zheng,
Qiwen Chen
et al.

Abstract: Solid-state lithium batteries hold great promise for next-generation energy storage systems. However, the formation of lithium filaments within the solid electrolyte remains a critical challenge. In this study, we investigate the crucial role of morphology in determining the resistance of garnet-type electrolytes to lithium filaments. By proposing a new test method, namely, cyclic linear sweep voltammetry, we can effectively evaluate the electrolyte resistance against lithium filaments. Our findings reveal a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…The SSR pellets also shorted at a “critical voltage” of ∼0.3–0.5 V, similar to the findings by others, , where LSV on LLZTO prepared by SSR displayed shorting at ∼0.4 V. In contrast, the critical voltage for the P2G pellets was more than doubled. P1, which had the highest relative density and ionic conductivity, showed a critical voltage of ∼1 V and a CCD of 1.11 mA/cm 2 .…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The SSR pellets also shorted at a “critical voltage” of ∼0.3–0.5 V, similar to the findings by others, , where LSV on LLZTO prepared by SSR displayed shorting at ∼0.4 V. In contrast, the critical voltage for the P2G pellets was more than doubled. P1, which had the highest relative density and ionic conductivity, showed a critical voltage of ∼1 V and a CCD of 1.11 mA/cm 2 .…”
Section: Resultssupporting
confidence: 88%
“…This is similar to the results and explanation reported by Cheng et al , where fine-grained LLZTO was prepared by attrition milling of SSR powders and displayed improved cycling performance compared to large-grained samples . Ouyang et al arrived at a similar conclusion and further highlighted the benefit of using small-grained LLZO with minimal pores to achieve higher CCD compared to that achieved using large-grained LLZO . Su et al also showed that fine-grained Ga-doped LLZO prepared using two-step sintering displayed better resistance to cracking after exposure to Li compared to samples with larger grains, some of which displayed abnormal grain growth .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations